Adat Wandalea dan Posambu Bagi Calon Ibu Pada Masyarakat Suku Buton Wally Di Dusun Kahena Negeri Batu Merah Kecamatan Sirimau Kota Ambon. - ima, Wa; Nindi, Wa (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2021)
The problem that the authors examine is whether the implementation of the Wandalea customs and postamble in the modern era in the adat implementation process is still by last year's implementation or whether there have been several processes removed to reconstruct the implementation of adat and discussions regarding the implementation of Wandalea customs and postamble and the values ​​contained in the process when the implementation of the adat Vandalia and posambu included items and tools used at the time of the implementation of adat, the authenticity of the tools remained or had been replaced with more modern tools compared to before. In the implementation of the Wandalea and Posambu adat, several things need to be considered; there is no debate because these two customs are still the same as last year; both were carried out only at that time. Again, some tools are replaced with woven baskets shaped like baskets and replaced with bamboo-woven plastic bags that are no longer approved. The problem that I will examine is how the process of implementing wandalea and posambu, as well as the objectives of carrying out traditional wandalea and posambu and values ​​contained in the process during the implementation of wandalea and posambu customs for the Buton Wally Tribe in Kahena Hamlet, Batu Merah, Sirimau District, Ambon City. Then, to filter the data in the field, the author uses observations and vice versa; observations are made to observe the process of implementing the Wandalea and Posambu customs and the impacts that occur if they do not carry out the process, while the author interviews with traditional leaders and community leaders in Kahena Hamlet, Batu Merah. The results obtained in this study, namely the Wandalea and Posambu customs, were carried out by the people of Buton Wally as a form of gratitude for the gift Allah SWT gave for adding new family members. Indigenous Vandalia and posambu become an obligation that must be carried out for couples waiting for new family members' arrival. The impact of adat Vandalia and posambu when it is not implemented is that children born from the womb of the mother will experience disability, abnormalities and other adverse effects. It must be underlined that this traditional procession is carried out on the first child of a married couple and is not done for the next child.